Variations in the molecular weight response of anionic polyacrylamides under different flocculation conditions. (2nd February 2018) - Costine, Allan; Cox, James; Travaglini, Shaun; Lubansky, Alex; Fawell, Phillip; Misslitz, Holger
Graphical abstract: Highlights: Continuous Couette flocculation of kaolin slurries with 7 PAMs of fixed anionicity but different MWs. Dosage-settling rate curves collected as a function of applied mixing, solids concentration, and liquor chemistry. Aggregate density-size relationship was determined by an image-analysis technique. Oscillatory rheology gave a better indication of PAM solution's potential performance than intrinsic viscosity. Abstract: The influence of applied mixing (intensity and duration), solids concentration, and liquor chemistry on the molecular weight (MW) response of seven anionic (30%) polyacrylamides was investigated in the flocculation of standard kaolin slurry at pH 8. Continuous flocculation was achieved in a Couette mixing device (CSIRO Shear Vessel) with a vertical flow-through arrangement allowing operator-independent settling rate measurements to be made under tightly controlled mixing conditions. It was found that the relative performance of the flocculants was strongly dependent on the hydrodynamic conditions prevailing during flocculation. The lower MWs gave a more dosage-effective response under mild mixing, producing denser, faster-settling aggregates than equivalent sizes produced with the higher MWs. Conversely, the larger sizes created by the higher MWs gave access to faster settling rates under intense mixing, except in the instance where polymer size and concentration led to chain entanglements. Sodium cations (<0.01 M) in the slurry favoured some degree of particle coagulation, whereas calcium cations had an adverse effect on settling rates even at low concentrations (<0.002 M), with the effects of a reduced bridging capacity most apparent in the lower MWs. The results advance the fundamental understanding of how chain length can substantially alter inter-particle bridging behaviour under different conditions, and thus provide a more robust basis for enhanced dewatering of clay suspensions through flocculant MW selection.